Photoelectrocatalytic degradation of Rhodamine B using N doped TiO2 thin Films. (2020) - Kothavale, V.P.; Patil, T.S.; Patil, P.B.; Bhosale, C.H.
Abstract: Highly transparent Nitrogen doped Titanium dioxide (N-TiO2 ) thin films are deposited onto glass/FTO substrates at optimized substrate temperature 450°C by using a simple chemical spray pyrolysis technique. The N-TiO2 thin films are characterized for their photoelectrochemical, structural, morphological and optical properties using PEC, XRD, SEM, and UV-Vis. spectrophotometer. The PEC study shows that both short circuit current (Isc) and open circuit voltage (Voc) for the doping concentration at 1.5 at. % are relatively maximum (Isc = 0.72 mA and Voc = 520 mV). X-ray diffraction studies show that films are polycrystalline with a tetragonal crystal structure. The scanning electron micrograph shows that the films are uniform, compact and with randomly distributedgrain size varying from 20 to 60 nm. The observed direct band gapsare about 3.4 and 3.37 eV for typical TiO2 and N-TiO2 thin films respectively.